DESA AKTIF: MEMBANGUN KOMUNITAS SEHAT MELALUI PENGEMBANGAN PROGRAM OLAHRAGA DAN KEBUGARAN DI TINGKAT DESA - Himawan Santoso, Indra; Sujarwanto; Mokhamad Nur Bawono; I Dewa Made Aryananda Wijaya Kusuma (FKIP UNIVERSITAS TUNAS PEMBANGUNAN SURAKARTA, 2026)
This community service program was conducted in Bejijong Village, Mojokerto Regency, with the aim of increasing community participation in sports activities and empowering youth through structured physical activities. The program included coordination with village officials and youth organizations, the implementation of the “Ayo Gerak” movement, group exercise sessions, sports games, special group activities, and health and sports workshops. This initiative aligns with Indonesia’s Asta Cita agenda, particularly the goals of improving human resource quality, enhancing productivity, and strengthening community-driven development at the village level. Furthermore, the program supports the achievement of key Sustainable Development Goals (SDGs), including SDG 3 (Good Health and Well-being), SDG 4 (Quality Education), SDG 11 (Sustainable Cities and Communities), and SDG 17 (Partnerships for the Goals). A participatory, community-based approach was applied, utilizing the revitalized sports facilities available in the village. The results indicate a significant increase in community enthusiasm, the development of active lifestyle habits, and improved awareness of the importance of physical activity for both physical and mental health. The program also strengthened collaboration between the village government, the university team, and the local community in developing a sustainable sports ecosystem. Overall, this initiative contributes meaningfully to the creation of an active, healthy, and productive village environment.